The impact of online task planning conditions on L2 utterance fluency and self-perceived fluency: a study of Chinese EFL learners - Han, Xu; Yahya, Yasir; Yap, Ngee Thai (Academy Publication, 2024)
This study examines the effects of online task planning conditions on L2 learners' utterance fluency and self-perceived fluency among Chinese EFL learners. Ninety participants were randomly assigned to Pressured Online Planning (POP), Unpressured Online Planning (UOP), and Hybrid Online Planning (HOP) groups. Participants completed a narrative task based on a Mr. Bean video clip under their respective planning conditions. Utterance fluency was measured using temporal and linguistic indicators, while self-perceived fluency was assessed through CEFR self-assessment and an Analytic Fluency Perception Scale. Results indicate that the hybrid condition yielded significantly higher speech and articulation rates, with fewer disfluencies compared to other conditions (p < .001). Notably, self-perceived fluency did not consistently align with objective measures or rater evaluations, particularly in the pressured condition. The study reveals complex relationships between task planning conditions, objective fluency measures, and learners' self-perceptions, contributing to our understanding of L2 speech production processes and informing task-based language teaching practices.